Suppression of SIV-specific CD4(+) T cells by infant but not adult macaque regulatory T cells: implications for SIV disease progression - Hartigan-O'Connor, Dennis J. (The Rockefeller University Press, 2007)
The impact of regulatory T cells (T reg cells) on the course of HIV and SIV disease is unknown. T reg cells could suppress protective antiviral responses and accelerate disease progression. Alternatively, these cells might block T cell activation and thereby limit viral replication as well as activation-associated immunopathology. Given the higher frequency of T reg cells known to be present during human fetal ontogeny, such influences may be most important in the context of perinatal infection. We found that infant macaques had higher fractions of CD4(+)CD25(+)CD127(low)FoxP3(+) T reg cells in the peripheral blood and in lymphoid tissues, and that these T reg cells showed greater in vitro suppressive activity on a per cell basis. Infant and adult macaques were infected with SIVmac251 to test the influence of the T reg cell compartment on SIV-specific immune responses. After infection with SIV, most (three out of four) infant macaques had persistently high viral loads, weak and transient SIV-specific CD4(+) and CD8(+) T cell responses, and rapid disease progression. T reg cells in the infant but not in the adult directly suppressed SIV-specific CD4(+) T cell responses, which were detectable only after depletion of T reg cells. In the case of both the infant and the adult macaque, T reg cells were not able to directly suppress SIV-specific CD8(+) T cell responses and had no apparent effect on T cell activation. In aggregate, these observations suggest that the T reg cell compartment of the infant macaque facilitates rapid disease progression, at least in part by incapacitating SIV-specific CD4(+) T cell responses.